How do you solve x^ { 2} - 6x = 7?

2 Answers
May 2, 2018

x = 7 or x = (-1)

Explanation:

Subtract 7 from both sides.
implies x^2 -6x - 7 =0
We need to factorize this expression by splitting its middle term.

impliesx^2 -7x +x - 7= 0
implies x(x-7)+1(x-7) = 0
implies (x-7)(x+1) = 0

implies x - 7 = 0 or x + 1= 0
implies x = 7 or x = (-1)

May 2, 2018

x=7
x=-1

Explanation:

x^2-6x=7 Subtract 7 from both sides:
x^2-6x-7=0
-7,1 are factors of -7 that add up to 6, so they will be factors:
(x-7)(x+1)=0 Using the 0 product property:
x-7=0
x=7
and
x+1=0
x=-1